In vitro Biphasic Effect of Honey Bee Venom on Basophils from Screened Healthy Blood Donors - Chirumbolo, Salvatore; Zanoni, Giovanna; Ortolani, Riccardo; Vella, Antonio (Allergy, asthma & immunology research, 2011)
Apis mellifera L. bee venom is the most studied hymenoptera allergen, but many aspects of its action on human basophils remain unclear. Allergologists seek evidence of the effectiveness of bee venom immunotherapy as this approach is the chosen treatment for systemic allergic reactions. The effect of bee venom on human basophils in vitro has not been studied in detail for many reasons, including the paucity of basophils in peripheral blood, inter-individual basophil response variability, and the reliability and predictability of basophil activation tests. We conducted a brief preliminary survey of the effect of Apis bee venom on healthy asymptomatic (non-allergic) subjects. A dose of an aqueous commercial extract of Apis bee venom as high as 10 µg/mL activated resting basophils (CD63=+80-90%, CD203c=+30%), while it inhibited the expression of CD63 (-50%) following basophil stimulation by the soluble agonists formyl-Met-Leu-Phe or anti-IgE. The activation of resting basophils appeared to be dose-related. Only when basophils were activated with an IgE-mediated agonist, did bee venom extract exhibit a possible priming mechanism at the lowest doses used only via CD63, while it was ineffective via CD203c. Autocrine interleukin-3 may play a role in the observed biphasic behavior.